Handbook of Thermal Science and Engineering 2018
DOI: 10.1007/978-3-319-26695-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in Micro- and Nanoscale Systems

Abstract: Small scale (micro/nanoscale) heat transfer has broad and exciting range of applications. Heat transfer at small scale quite naturally is influenced-sometimes dramatically-with high surface area to volume ratios. This in effect means that heat transfer in small scale devices and systems is influenced by surface treatment and surface morphology. Importantly, interfacial dynamic effects are at least non-negligible and there is a strong potential to engineer the performance of such devices using the progress in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 144 publications
0
1
0
Order By: Relevance
“…Energy transfer in micro/nano heat exchangers is primarily governed by two mechanisms, i.e., conduction and convection [173]. However energy transport at these scales is usually associated with multiple nonequilibrium processes due to the similarity in the system length scales with the molecular mean free path and process time scales being lower than the relaxation time [174].…”
Section: Micro/nano Heat Exchangermentioning
confidence: 99%
See 1 more Smart Citation
“…Energy transfer in micro/nano heat exchangers is primarily governed by two mechanisms, i.e., conduction and convection [173]. However energy transport at these scales is usually associated with multiple nonequilibrium processes due to the similarity in the system length scales with the molecular mean free path and process time scales being lower than the relaxation time [174].…”
Section: Micro/nano Heat Exchangermentioning
confidence: 99%
“…Changes in the interfacial area between the fluid and the solid caused by bubble entrainment can also affect the transport across surfaces. Chemical reactions and adsorption are impacted by an increase in the interfacial area [174,190].…”
Section: Bubble Entrainmentmentioning
confidence: 99%
“…The research reported here originated through a UK-Brazil Newton Fund-FAPERJ collaborative development project, offering a holistic approach to address the complex nexus challenges from the societal demand for food, water, energy and need for environmental care. The motivation involved a combined system, harnessing electrical energy from high efficiency water cooled HCPVs and using the resulting waste heat for water desalination and continuous biodiesel production, making use of nano and micro-scale transport phenomena analysis tools recently employed in different thermal engineering applications [8][9][10][11]. The original aspects of the present research includes problem formulation and simplification strategies, modern analytical-numerical solution methods for differential equations, parametric and functional identification through inverse analysis, symbolic computation tools, nano and micro-fabrication, non-intrusive optical techniques in micro-scale heat and fluid flow, employed individually or jointly, as needed to answer the basic questions raised by the applications to be advanced.…”
Section: Introductionmentioning
confidence: 99%